2010
DOI: 10.1117/1.3316296
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination analysis of human lung cancer cells associated with histological type and malignancy using Raman spectroscopy

Abstract: Abstract. The Raman spectroscopic technique enables the observation of intracellular molecules without fixation or labeling procedures in situ. Raman spectroscopy is a promising technology for diagnosing cancers-especially lung cancer, one of the most common cancers in humans-and other diseases. The purpose of this study was to find an effective marker for the identification of cancer cells and their malignancy using Raman spectroscopy. We demonstrate a classification of cultured human lung cancer cells using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 29 publications
1
68
1
1
Order By: Relevance
“…Visibly, it can be seen that the mean spectra of the nucleolar, nuclear and cytoplasmic regions are somewhat different, and discriminating peaks (indicated by highlighted regions in Fig. 1) at, for example, 1578, 1095, 830 and 795 cm −1 can be allocated to nucleic acids which correspond respectively to vibrations of the DNA bases adenine and guanine, DNA PO 2 − symmetric stretching, ribose phosphate and DNA backbone O-P-O stretching, 44,45 while others at 1300 (CH deformation) and 717 cm −1 (CN + (CH 3 ) 3 stretching) are associated with lipid components of the cell membrane, which are also observable in subsequent spectra of the nuclear and nucleolar regions, although more prominently in the spectra of the cytoplasmic region. The DNA bands at 1095 cm −1 and 830 cm −1 indicate that the DNA is in B form and one at 813 cm −1 corresponds to DNA A form.…”
Section: Raman Micro Spectroscopymentioning
confidence: 99%
“…Visibly, it can be seen that the mean spectra of the nucleolar, nuclear and cytoplasmic regions are somewhat different, and discriminating peaks (indicated by highlighted regions in Fig. 1) at, for example, 1578, 1095, 830 and 795 cm −1 can be allocated to nucleic acids which correspond respectively to vibrations of the DNA bases adenine and guanine, DNA PO 2 − symmetric stretching, ribose phosphate and DNA backbone O-P-O stretching, 44,45 while others at 1300 (CH deformation) and 717 cm −1 (CN + (CH 3 ) 3 stretching) are associated with lipid components of the cell membrane, which are also observable in subsequent spectra of the nuclear and nucleolar regions, although more prominently in the spectra of the cytoplasmic region. The DNA bands at 1095 cm −1 and 830 cm −1 indicate that the DNA is in B form and one at 813 cm −1 corresponds to DNA A form.…”
Section: Raman Micro Spectroscopymentioning
confidence: 99%
“…Notingher et al 6 used a Raman microspectrometer to characterize living cells attached to bioinert silica materials. Oshima et al 7 measured Raman spectra of single-live human lung cancer cells and successfully discriminated them by multivariate analysis. Hartmann et al 8 studied the effects of an anticancer drug by Raman spectroscopy and observed changes in DNA/RNA and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches such as PCA or K-means clustering are commonly used for the analysis of large amounts of data, allowing a discrimination of different samples or regions of a sample, according to differences in their biochemical content, and identification of the spectral features which manifest the highest degree of variability [1,7,[31][32][33]. Although these methods are used routinely and are quite well developed, the question of the relevance and molecular specificity of the information contained in the data remains largely unaddressed.…”
Section: Introductionmentioning
confidence: 99%